THE CORRELATION BETWEEN COVID-19 KNOWLEDGE AND COMMUNITY ANXIETY AND DEPRESSION IN INDONESIA’S RED ZONE DURING THE PANDEMIC - Prakoso, Denny Anggoro; Dewi, Anis Prima; Azzahra, Anindya Faradila (Universitas Muhammadiyah Ponorogo, 2025)
The rapid spread of Covid-19 has impacted physical and psychological well-being globally, including in Indonesia. Anxiety and depression are prevalent psychological challenges during the pandemic. This study aimed to assess the relationship between Covid-19 knowledge and psychological outcomes—anxiety and depression—among residents in Indonesia's high-risk